Dietary beta-hydroxy-beta-methyl butyrate supplementation improves meat quality of Bama Xiang mini-pigs through manipulation of muscle fiber characteristics. (January 2022) - Zheng, Changbing; Zhang, Shiyu; Duan, Yehui; Li, Fengna; Song, Bo; Guo, Qiuping; Zheng, Jie; Zhang, Lingyu; Lian, Guoqi; Duan, Geyan
Graphical abstract: Highlights: HMB supplementation (0.13%) decreases subcutaneous fat accumulation. HMB supplementation (0.13%) improves meat quality of pigs. HMB supplementation promotes muscle fiber type switching from type II to type I. HMB's beneficial effects were associated with AMPKα-Sirt1 signaling. Abstract: To analyse the effects of dietary beta-hydroxy-beta-methyl butyrate (HMB) on meat quality, 32 Bama Xiang mini-pigs was selected and fed 1 of 4 diets for 60 days: HMB deficient group (0%, control), low, moderate, and high levels of HMB group (0.13%, 0.64%, 1.28%, respectively). We found quadratic effects for backfat thickness and lean percentage ( P  < 0.05) as well as a* value in selected muscles (0.05 <  P  < 0.10), and the best effects were noted in the 0.13% HMB group. Moreover, dietary HMB quadratically increased the mRNA expression levels of MyHC I, AMPKα, and Sirt1 in selected muscles, the highest values were observed in the 0.13% HMB group. These results suggest that low HMB levels improved meat quality of Bama Xiang mini-pigs via the changed myofiber characteristics induced by AMPKα-Sirt1 axis.